2016
DOI: 10.5772/64163
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Socially Assistive Robotics in Rehabilitation for Children with Cerebral Palsy: A Review

Abstract: Robotic assistive technology is today widely used in rehabilitation. Social assistive robotics (SAR) is one of the developing areas of research with potential advantages for areas involving elderly care, people with cognitive impairment, rehabilitation for people with physical disabilities and for educational purposes. Cerebral palsy (CP) is a common neurological disorder among children that impairs motor function and may involve cognitive function. The use of social assistive robotic technology serves as a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…Tipo 1: Robots que usan habilidades motoras del paciente; es decir, establecen contacto con el paciente mediante la aplicación de fuerza como comando para lograr ciertas tareas, y Tipo 2: Robots que motivan al paciente en un ambiente controlado para imitar o seguir ciertos ejercicios, sin tener contacto. Esta última es una aplicación de la rehabilitación robótica innovadora que involucra al niño y lo hace parte de la terapia; este es el campo de los robots sociales 50 que permiten la creación de personajes artificiales, de esta manera los niños logran tener un compañero o interlocutor mucho más accesible. También, los robots sociales poseen dos perspectivas de diseño [45][46] , la primera son los inspirados en sistemas biológicos; y la segunda se denomina "Diseño funcional", donde se busca alcanzar un robot "socialmente inteligente".…”
Section: Resultados Y Discusiónunclassified
“…Tipo 1: Robots que usan habilidades motoras del paciente; es decir, establecen contacto con el paciente mediante la aplicación de fuerza como comando para lograr ciertas tareas, y Tipo 2: Robots que motivan al paciente en un ambiente controlado para imitar o seguir ciertos ejercicios, sin tener contacto. Esta última es una aplicación de la rehabilitación robótica innovadora que involucra al niño y lo hace parte de la terapia; este es el campo de los robots sociales 50 que permiten la creación de personajes artificiales, de esta manera los niños logran tener un compañero o interlocutor mucho más accesible. También, los robots sociales poseen dos perspectivas de diseño [45][46] , la primera son los inspirados en sistemas biológicos; y la segunda se denomina "Diseño funcional", donde se busca alcanzar un robot "socialmente inteligente".…”
Section: Resultados Y Discusiónunclassified
“…In the expertise condition, the robot introduced itself as being programmed by physiotherapists, asked questions concerning the participants previous experience with therapy and provided a number of facts about the exercise to be done/the condition it was designed to treat. This information was taken from public NHS 3…”
Section: B Experimental Conditionsmentioning
confidence: 99%
“…entertainment. Example applications include exercise instruction and encouragement (for general fitness/sports [2] and in various types of therapy [3] [4]), for weight loss coaching [5] and other forms of positive behaviour change (e.g. reducing energy consumption [6]).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational and physical therapists as well as speech language pathologists have long used play-like activities to engage children in therapeutic interventions. Motor skills such as reaching and grasping, language development activities involving play scenarios, and the use of toys to enhance overall engagement in therapeutic behaviors are just a few examples [8][9][10][11][12]. It has been suggested that toys may have a greater impact for children with severe disabilities when they have educational value; however, young children with disabilities are less likely to actively engage with objects or other people, which results in the need for more frequent and exciting play opportunities [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…To meet this need, toys specifically adapted for better educational access and greater interaction-to provide multisensory input and allow for repetitive interaction-have been developed for children with all kinds of disabilities [13][14][15][16]. Additionally, assistive technologies designed for adapted play and social interaction can prove to be fundamental in enabling children with physical disabilities to play, as well as facilitate learning in those with cognitive disabilities [9,17].…”
Section: Introductionmentioning
confidence: 99%